(untitled) (The Research of Medical Science Review, 2024)
Background: Telenursing is considered a time-saving and effective source of care delivered to patients that cannot approach the health care facilities. Telenursing needs clinical expertise with good knowledge and who works independently for sick people. The aim of the study was to assess the telenursing perception and knowledge among Nurses in Peshawar, Khyber Pakhtunkhwa. Methodology: An analytical cross-sectional study was carried out in district Peshawar Khyber Pakhtunkhwa. Participants were employed from Lady Reading Hospital, Khyber Teaching Hospital and Hayatabad Medical Complex Peshawar. Data was collected from overall 180 participants using a validated questionnaire. Results: The mean age of the participants was 28.86 years. 86.1% of the participants were female and 77.8% of the participants were diploma holders. Overall, 66% of the participants were having “Moderate knowledge”, 26% of the participants were reported good while only 8% of the participants were reported Poor knowledge. Similarly, 85% of the participants were reported positive perceptions while 15% were reported negative perceptions towards telenursing. There was a significant association (p= 0.015) between the level of knowledge and the perception of nurses towards telenursing. Conclusion: Telenursing services is an effective and time-saving modern technology that plays a dynamic role in patient care and allows them to access nursing services at home. Nurses had positive perceptions and moderate level of knowledge regarding telenursing.